(untitled) (Journal of the Entomological Research Society, 2024)
The tea lace bug, Stephanitis chinensis Drake, 1948, a notorious pest, inflicts significant damage on commercial tea cultivation and ornamental gardens across China. In this study, we investigated the genetic diversity, population structure, and demographic history of S. chinensis based on the genetic and phylogenetic analysis of mitochondrial cytochrome c oxidase I (cox1) sequences. The dataset exhibited 453 polymorphic sites, 315 parsimony informative sites, and 138 singleton variable sites, attesting to the species’ genetic complexity. Haplotype diversity varied across populations, with the highest in Ziyang County of Shaanxi Province (SXZY) and lowest in Yongchuan District of Chongqing City (CQYC). Genetic differentiation was primarily within populations, while some pairs showed significant divergence, indicative of geographic barriers and local adaptation. Inconsistent signals from neutrality tests and mismatch distribution analysis suggested historical stability interspersed with growth or bottleneck events. Phylogenetic analysis depicted distinct haplotype clusters, with Mabian County of Sichuan province (SCMB) forming a unique clade. The haplotype network emphasized geographic uniqueness while highlighting shared ancestry between Yongchuan District of Chongqing City (CQYC) and Guwen County of Hunan Province (HNGW). These findings illuminate S. chinensis’ ecological adaptability, historical dynamics, and potential for adaptive responses to agricultural practices. In addition, the results indicated important implications for pest management, genetic conservation, and the broader understanding of the species’ evolutionary trajectory.